2017
DOI: 10.3847/1538-3881/aa9bf2
|View full text |Cite
|
Sign up to set email alerts
|

FUV Spectral Signatures of Molecules and the Evolution of the Gaseous Coma of Comet 67P/Churyumov–Gerasimenko

Abstract: The Alice far-ultraviolet imaging spectrograph onboard Rosetta observed emissions from atomic and molecular species from within the coma of comet 67P/Churyumov-Gerasimenko during the entire escort phase of the mission from 2014 August to 2016 September. The initial observations showed that emissions of atomic hydrogen and oxygen close to the surface were produced by energetic electron impact dissociation of H 2 O. Following delivery of the lander, Philae, on 2014 November 12, the trajectory of Rosetta shifted … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 35 publications
(59 reference statements)
3
36
1
Order By: Relevance
“…23, the CO/H 2 O ratios measured by MIRO (r h < 2.4 AU) are all below 1%. Measurements with the Alice instrument shortly after perihelion lead to CO/H 2 O ∼ 0.5% (Feldman et al 2018), in agreement with MIRO determinations. A low (<1%) CO/H 2 O abundance near perihelion is also consistent with the upper limit measured from infrared spectra obtained by VIRTIS (Bockelée-Morvan et al 2016).…”
Section: Data Based On Analysis Of Nadir Pointingssupporting
confidence: 84%
“…23, the CO/H 2 O ratios measured by MIRO (r h < 2.4 AU) are all below 1%. Measurements with the Alice instrument shortly after perihelion lead to CO/H 2 O ∼ 0.5% (Feldman et al 2018), in agreement with MIRO determinations. A low (<1%) CO/H 2 O abundance near perihelion is also consistent with the upper limit measured from infrared spectra obtained by VIRTIS (Bockelée-Morvan et al 2016).…”
Section: Data Based On Analysis Of Nadir Pointingssupporting
confidence: 84%
“…Our calculated volume emission rates clearly show that photodissociation of H 2 O contributes to the total H I Lyman-β emission by an order of magnitude higher compared to solar resonance fluorescence close to the cometary surface (see Figure 3). Feldman et al (2018) also found that the contribution from resonance scattering for H I Lyman-β emission is negligible in the Alice observations. It should be noted that the Rosetta was orbiting at radial distances around 90 km on 2015 March 29 while Alice was making nadir observations, hence the contribution from solar resonance fluorescence in the nadir observed HI Lyman-β intensity can be neglected.…”
Section: Implications For Formation Processes Of H I O I and C I Emmentioning
confidence: 72%
“…This calculation show that resonant scattering of atomic oxygen can also determine the oxygen emission ratio when substantial atomic oxygen is present in the inner coma. Feldman et al (2018) also noticed in the limb observation around the perihelion made on 2015 Aug 19 that resonance fluorescence is important excitation source in producing OI 1304 Å emission. Global kinetic models such as Tenishev et al (2008), which accounts for strong momentum exchange between hot oxygen atoms to surrounding water molecules, can determine accurate atomic oxygen densities close to the nucleus which is not possible by our one-dimensional approach.…”
Section: Atomic Oxygen Line Emission Intensity Ratiomentioning
confidence: 81%
See 2 more Smart Citations